Savaş Fotoğrafı Tarihinde Dijitalleşme Süreci Ve Fotografik Etkisi - Yavuz, Uğur Günay (The Turkish Online Journal of Design Art and Communication, 2012)
From the Crimean War photographs that Roger Fenton went by a coach and authenticated to today, the war photography has showed a remarkable and rapid evolution in sense of technology especially after 1975 when the digital technology has entered in our daily lives and pervaded. As time goes by, instead of carrying a photo camera, cellular phones with the photo camera option has become a preference, yet became a standard. A Pulitzer Award winner newspaper photographer Damon Winter, assigned by New York Times to observe the U.S. operations in Afghanistan has awarded in “Pictures of the Year” Contest by the pictures that he has taken by his cellular phone with the help of a software called “Hipstamatic”. The utmost in the digitalization in the photography, by all means, is also bringing a wide range of debates with it. By this study, the history of war photography will be reviewed from the first day to today and will be analysed with the photographs including the 1st and 2nd World Wars, Vietnamese Conflict, the Iraq War where digital photography was used and thus the photographic effects of digitalization on the war photography is aimed to be revealed.
Keywords: Digitalization; Photograph; War Photography; Dijitalleşme; Fotoğraf; Savaş Fotoğrafçılığı